THE USE OF COMIC STRIPS TO IMPROVE STUDENTS' READING COMPREHENSION OF NARRATIVE TEXT FOR THE TENTH GRADERS AT SMK WAHID HASYIM IN THE ACADEMIC YEAR 2023/2024 - Suci Ni’matur Rosyidah; Bariqotul Hidayah (J-Shelves of Indragiri (JSI), 2024)
This research aimed to enhance reading comprehension among tenth-grade students at SMK Wahid Hasyim. They faced challenges with understanding English texts, including a limited vocabulary, low scores, and a general lack of interest in English reading materials. This research focused on enhancing reading comprehension skills in narrative texts through comic strips. The study involved  33 students from the Office Management and Business Services program and used a collaborative Classroom Action Research (CAR) design. Various instruments, including modules, observation sheets, field  note, and questionnaires, were employed, with collaboration from the classroom English teacher. Conducted in two of cycles planning, implementing, observing, and reflecting. The research showed initial results with 24.24% of students meeting the mastery level. After revising the instructional materials, the second cycle showed a significant improvement, with 90.91% achieving a perfect score. These findings demonstrate that comic strips are effective in improving reading comprehension among tenth graders, confirming their potential as valuable educational tools.